Hydrogen Evolution: Perpendicularly Oriented MoSe2/Graphene Nanosheets as Advanced Electrocatalysts for Hydrogen Evolution (Small 4/2015). Issue 4 (January 2015) - Mao, Shun; Wen, Zhenhai; Ci, Suqin; Guo, Xiaoru; Ostrikov, Kostya (Ken); Chen, Junhong
<x xml:space="preserve">Abstract</x> MoSe2 nanosheets are vertically grown on a 3D graphene network by Z. Wen, J. Chen, and co‐workers on page 414 as electrocatalysts for the hydrogen evolution reaction (HER). The vertical orientation is beneficial for maximizing exposed active edges to protons, facilitates ions/electrolyte transport at the electrode interface, and minimizes agglomeration and restacking of the nanosheets, while the underlying grapheme improves the electrical contact between the MoSe2 catalyst and the electrode. The resulting hybrids show a improved catalytic activity compared with MoSe2 nanosheets alone. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>